2020
DOI: 10.3389/fonc.2020.00147
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus—Related Cognitive and Affective Impairments in Patients With Breast Cancer—A Systematic Review

Abstract: Background: Although improvements in medical treatment lead to a steadily rising survival rate of breast cancer patients (BCP), it is associated with a decrease in cognitive and affective function. The hippocampus, a brain region with a high influence on both cognitive and affective function, is increasingly becoming the focus of current research because of its high vulnerability to adverse direct (chemotherapeutic agents, endocrine therapeutic agents, and radiation) or indirect (stress and other psycho-social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…It turned out that machine learning techniques were superior to conventional regression-based analyses in terms of the predictive performance. In accordance with various studies investigating the prognostic factors of PDAC [ 11 , 31 , 32 ], lymph node status (N-stage), vascular invasion and CA199 are independent predictors for both 1- and 2-year relapse. Although the RF model had the highest AUROC in the training set, the SVM model and KNN model showed better robustness to predict 1- and 2-year relapse in the validation set, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…It turned out that machine learning techniques were superior to conventional regression-based analyses in terms of the predictive performance. In accordance with various studies investigating the prognostic factors of PDAC [ 11 , 31 , 32 ], lymph node status (N-stage), vascular invasion and CA199 are independent predictors for both 1- and 2-year relapse. Although the RF model had the highest AUROC in the training set, the SVM model and KNN model showed better robustness to predict 1- and 2-year relapse in the validation set, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Altered brain connectivity due to chemotherapy can disrupt the hippocampus's structure and function, which could directly contribute to impairment in different cognitive domains, particularly long-term and short-term memory. Changes in the prefrontal cortex were also found to be associated with CICI manifesting alterations in memory, attention, and executive functions Peukert et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both animal and preclinical clinical studies have revealed that the hippocampus and the frontal lobes are particularly vulnerable to the adverse effects of chemotherapy ( Winocur et al, 2018 ; Peukert et al, 2020 ). As early as 2004, Rzeski et al (2004) found that cytotoxic drugs could extensively damage the hippocampal dentate gyrus of 7-day-old rats.…”
Section: Discussionmentioning
confidence: 99%